Deciphering the developmental trajectory of tissue-resident Foxp3+ regulatory T cells - Alvarez, Fernando; Liu, Zhiyang; Bay, Alexandre; Piccirillo, Ciriaco A. (Frontiers in Immunology, 2024)
FoxP3 + TREG cells have been at the focus of intense investigation for their recognized roles in preventing autoimmunity, facilitating tissue recuperation following injury and orchestrating a tolerance against innocuous non-self-antigens. To perform these critical tasks, TREG cells undergo deep epigenetic, transcriptional, and post-transcriptional changes that allow them to adapt to conditions found in tissues both at steady-state and during inflammation. The path leading TREG cells to express this specialized phenotype in the tissues starts during thymic development, involves epigenetic and transcriptional events resulting from TCR engagement in the periphery and the presence of polarizing signals that orchestrate their functional fate. However, this process is highly regulated and requires TREG cells to adopt strategies to avoid losing their regulatory program altogether. Here, we review the origins of tissue resident TREG cells, from their thymic and peripheral development to the transcriptional regulators involved in their tissue residency program. In addition, we discuss the distinct signalling pathways that engage the inflammatory adaptation of tissue-resident TREG cells, and how they relate to their ability to recognize tissue and pathogen-derived danger signals.